Beneficial physiological effects with blackcurrant intake in endurance athletes - Theodorus Willems, M. E.; Myers, S. D.; Gault, M. L.; Cook, M. D. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
Blackcurrant contains anthocyanins, known to influence vasorelaxation and peripheral blood flow. We examined the effects of 7 days intake of Sujon New Zealand blackcurrant powder (6g/day) on the lactate curve, maximum oxygen uptake, and cardiovascular responses at rest and during cycling. Thirteen trained triathletes with >3 yrs experience (8 men, age: 38 ± 8 yrs, body mass: 71 ± 9 kg, BF%: 19 ± 5%, mean ± SD) performed two incremental cycling protocols with recording of physiological and cardiovascular responses (Portapres Model 2). Cardiovascular function was also measured in rest. Experimental design was doubleblind, placebo-controlled, randomized and cross-over (wash-out 4 wks). Data were analyzed with two-tailed t tests and 2-way ANOVA and significance accepted at p < .05. Plasma lactate was lower at 40%, 50%, 60% and 70% of maximum power by 27%, 22%, 17% and 13%. Intensity at 4 mmol·L-1 OBLA was 6% higher with blackcurrant without effect on heart rate and oxygen uptake. Maximum values of oxygen uptake, heart rate and power were not affected by blackcurrant, but obtained with 14% lower lactate. In rest, blackcurrant increased stroke volume and cardiac output by 25% and 26%, and decreased total peripheral resistance by 16%, with no changes in blood pressure and heart rate. Cardiovascular responses during exercise at 40%, 50%, 60%, 70% and 80% intensity were not affected. Sujon New Zealand blackcurrant powder affects lactate production and/or clearance during exercise. Sujon New Zealand blackcurrant powder affects physiological and cardiovascular responses in rest and during exercise that may have implications for exercise performance.